Sustainable tourism supported by the drafting of the Crossborder Sustainable Mobility Plan (PTMS) between southern Italy and Epirus in Greece - Fabio Carlucci; Domenico Gattuso; Luigi Senatore; Barbara Trincone; Elisabetta Venezia (European Scientific Journal, ESJ, 2024)
The drafting of a cross-border Sustainable Mobility Plan, developed within the framework of the European project, financed by the Interreg Greece-Italy Cooperation Programme 2014-2020, highlights the importance of a synergic and systemic approach to cope with the need to agree on sustainable accessibility models at international and local level for the development of tourism that is sensitive to the environmental, social and economic needs of the territories. The imperative from which the research starts is the imminent urgency of providing systemic sustainability solutions for which transport assumes a central role. The Cross-Border Sustainable Mobility Plan (PTMS) was drawn up taking into account international, national and local transport plans and programmes, with particular attention to existing SUMPs (Sustainable Urban Mobility Plans), and then proposes alternative solutions to the most polluting ones and lays the foundations for the possible activation of new maritime lines connecting southern Salento (Italy) with Epirus (Greece).